Scalable Production and Multifunctional Coating of Gold Nanostars for Catalytic Applications - Silvia Nuti; Adrián Fernández-Lodeiro; Inmaculada Ortiz-Gómez; Carlos Lodeiro; Javier Fernández-Lodeiro (Nanomaterials)
Gold nanostars (AuNSTs) stabilized with adenosine monophosphate (AMP) were synthesized using a scalable method, achieving a 30-fold yield increase compared to previous studies using AMP as a shaping agent, while also reducing the reaction time to 3 h. The AuNSTs were coated with mesoporous silica (mSiO2) via a robust approach, producing the AuNSTs@mSiO2 nanoparticles (NPs) with tunable thicknesses and consistent optical properties for a range of morphologies. The NPs were additionally coated with platinum (Pt) before synthesizing the mSiO2 layer, facilitating a comparative analysis of catalytic activity. The catalytic performance of the bare AuNSTs, the AuNSTs@mSiO2, and the AuNSTs@Pt@mSiO2 was evaluated through methylene blue reduction, confirming the gold core as the primary catalytic source. The AuNSTs@Pt@mSiO2 exhibited enhanced activity, highlighting the potential of the mSiO2 coatings. Additionally, solid-phase catalytic tests using 3,3′,5,5′-tetramethylbenzidine (TMB) on cellulose discs demonstrated the effectiveness of these NPs under diverse conditions. These findings showcase the versatility and broad catalytic potential of silica-coated NPs for solution- and solid-phase applications.